Can argyrophilic nucleolar organizing region-associated protein amount be used for the detection of cardiac damage?. (March 2016) - Kandiş, H; Afacan, MA; Eröz, R; Colakoglu, S; Bayramoglu, A; Oktay, M; Saritas, A; Colak, S; Kaya, M; Kara, İH
Introduction: Carbon monoxide (CO) is a colorless, tasteless, odorless, nonirritant gas and CO poisoning affects all organ systems. Aim: We aimed to detect any possible effects of CO exposure on the argyrophilic nucleolar organizing region (AgNOR)-associated protein synthesis of heart cells and whether there is any relationship between AgNOR protein amount and both carboxyhemoglobin (COHb) level and histopathological evaluation methods used for the detection of damage in heart tissue after CO exposure. Materials and Methods: The rats were divided into four groups (control, 1000, 3000, and 5000 ppm), each containing six rats. After CO intoxication, COHb levels were measured and the animals were killed on the 7th day. AgNOR staining was performed in the heart tissue. One hundred nuclei per rat were evaluated, and total AgNOR area/nuclear area and mean AgNOR number were analyzed for each nucleus. The CO exposure groups had significantly higher AgNOR values than the control group ( p < 0.0001). According to cardiomyopathy (CMY) scoring methods, the differences between groups 3 and 4 and groups 1 and 2 were significant ( p < 0.05). A significant positive correlation between AgNOR values and both CMY and COHb levels were detected. Conclusion: The detection of AgNOR protein amount may give information about the CMY levels and be used to detect the CO intoxication levels instead of COHb in later periods.